Plan de comunicación interna de Perú InterCargo - Castañeda Silva, Aida Pamela (2021)
Peru InterCargo (PIC), one of the three most important logistics operators in Peru with more than 40 years in the market, has a lack of commitment from PIC leaders regarding organizational culture. Due to this, there is a high job rotation in the teams despite the context of the pandemic. Therefore, this work proposes the development of an internal communication plan in order to improve the commitment of its leaders and workers with the company and its organizational culture.